2015
DOI: 10.1099/vir.0.000054
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy serum facilitates hepatitis E virus replication in vitro

Abstract: Hepatitis E virus (HEV) infection causes high mortality in pregnant women. However, the pathogenic mechanisms of HEV infection in pregnant women remain unknown. In this study, the roles of pregnancy serum in HEV infection were investigated using an efficient cell culture system. HEV infection was exacerbated by supplementing with pregnancy serum, especially theat in third trimester of pregnancy. Oestrogen receptors (ER-a and ER-b) were activated in cells supplemented with pregnancy serum and were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…Our previous study confirmed that pregnancy serum in the third trimester of pregnancy significantly facilitates HEV replication in vitro; however, the mechanism remains unclear. In this study, significantly higher oestradiol was found in HEV‐infected pregnant women in their third trimester of pregnancy compared with uninfected pregnant women.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our previous study confirmed that pregnancy serum in the third trimester of pregnancy significantly facilitates HEV replication in vitro; however, the mechanism remains unclear. In this study, significantly higher oestradiol was found in HEV‐infected pregnant women in their third trimester of pregnancy compared with uninfected pregnant women.…”
Section: Introductionsupporting
confidence: 62%
“…The suspension was then stored in liquid nitrogen until use. The viral genomic titres, which comprised 1.0 × 10 6 copies/mL, were determined using quantitative real‐time PCR (qRT‐PCR), as described in previous studies …”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of estrogen, progesterone, and β-human chorionic gonadotrophin in HEV-positive pregnant FHF women are higher than in HEV-negative pregnant FHF women or controls [93]. An in vitro study showed that serum from pregnant women, especially those in the third trimester, enhanced the replication of HEV by inhibiting estrogen receptor and type I IFN expression [94]. While some studies have found that the high HEV RNA concentrations in HEV-infected pregnant women were associated with a poor outcome [89,95]; another study by Saravanabalaji et.…”
Section: Pathogenesis Of Fulminant Hepatitismentioning
confidence: 99%
“…Interferon type I, particularly interferon beta, shows late up regulation when supplemented with HEV‐infected cells with serum of pregnant women in the third trimester, indicating delayed IFN‐β expression facilitates viral copying. The result suggests pregnancy serum increases the HEV multiplication by repressing oestrogen receptors and interferon type I in initial stage of disease …”
Section: Discussionmentioning
confidence: 95%